2015
DOI: 10.1186/s12868-015-0170-6
|View full text |Cite
|
Sign up to set email alerts
|

A functional comparison of the domestic cat bitter receptors Tas2r38 and Tas2r43 with their human orthologs

Abstract: BackgroundDomestic cats (felis catus) have a reputation for being rather unpredictable in their dietary choices. While their appetite for protein or savory flavors is consistent with their nutritional needs, their preference among protein-sufficient dietary options may relate to differences in the response to other flavor characteristics. Studies of domestic cat taste perception are limited, in part, due to the lack of receptor sequence information. Several studies have described the phylogenetic relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
3
24
0
Order By: Relevance
“…We have repeatedly found no effects of these DMSO levels on airway cell Ca 2ϩ or NO signaling (12,14,15,31,101,102), including here. Moreover, other studies have supported a specific role for T2R38 in AHL detection (103)(104)(105)(106) and also found no activation of endogenous T2R38 by 0.1% DMSO (107), as used here.…”
Section: Bitter Taste Receptors Detect Bacterial Quinolonessupporting
confidence: 75%
See 1 more Smart Citation
“…We have repeatedly found no effects of these DMSO levels on airway cell Ca 2ϩ or NO signaling (12,14,15,31,101,102), including here. Moreover, other studies have supported a specific role for T2R38 in AHL detection (103)(104)(105)(106) and also found no activation of endogenous T2R38 by 0.1% DMSO (107), as used here.…”
Section: Bitter Taste Receptors Detect Bacterial Quinolonessupporting
confidence: 75%
“…A recent study reported that T2R10 and T2R14, not T2R38, respond to some AHLs when expressed in HEK293 cells (46). The reason for this discrepancy is not yet clear, as other studies have shown that T2R38 detects AHLs (103)(104)(105)(106). We hypothesize that cloned receptor polymorphisms and/or different methodologies (microscopy versus plate reader assays) may contribute to some differential results observed.…”
Section: Bitter Taste Receptors Detect Bacterial Quinolonesmentioning
confidence: 78%
“…Nevertheless, as the cat Tas2r38 ortholog shows insensitive PTC responsiveness and no PROP responses (72,73) we assumed the existence of a common ancestral TAS2R38 ortholog permissive for PTC/ PROP responses. Of course, the existence of further critical positions for PTC/PROP responses cannot be ruled out and may contribute significantly.…”
Section: Substancementioning
confidence: 99%
“…There are four to six T2R genes in fish and three in chickens, but 21-42 in mammals and 49 in frogs (Shi and Zhang 2006), indicating a species-or lineage-specific gene duplication event. In mammals, the evolutionary relationships of T2R gene families have been described in detail (Conte et al 2003;Fischer et al 2005;Go et al 2005;Lei et al 2015;Sandau et al 2015;Wang et al 2004). Five T2R protein groups existed prior to the divergence of the primate and rodent lineages (Conte et al 2003;Shi et al 2003), and the species-or lineage-specific gene duplication and pseudogenization were shown to play an important role in altering of the T2R gene repertoire in individual primate species (Go et al 2005;Zhao et al 2010).…”
Section: Figmentioning
confidence: 99%